2014
DOI: 10.5539/ass.v10n18p122
|View full text |Cite
|
Sign up to set email alerts
|

Urban Community Willingness to Pay for Improved Solid Waste Management in Malaysian Municipality: A Choice Modeling Approach

Abstract: The management of solid waste in urban areas is a critical issue for some developing countries especially in Asia which requires immediate attention. This study attempts to make an analysis and assessment of public attitudes and behaviour towards the improvement of urban solid waste management offered by a municipality in Malaysia by looking at the people's willingness to pay (WTP) for the improved services. Seremban Municipality, one of the most important municipalities in Malaysia, has been chosen for this s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 8 publications
3
10
0
Order By: Relevance
“…However, the gender variable is statistically insignificant and we could not derive any relationship, but the finding is consistent with other similar studies [15,19,21,31]. Some studies found the age variable to have a positive relationship with the maximum WTP amount [21,30,33]. However, this study expected that younger household heads, who could be more educated and aware of the importance of proper waste management, would pay more for improved waste collection service as found by Padi et al [15].…”
Section: Factors Influencing Amount Of Money That Households Are Willsupporting
confidence: 82%
See 2 more Smart Citations
“…However, the gender variable is statistically insignificant and we could not derive any relationship, but the finding is consistent with other similar studies [15,19,21,31]. Some studies found the age variable to have a positive relationship with the maximum WTP amount [21,30,33]. However, this study expected that younger household heads, who could be more educated and aware of the importance of proper waste management, would pay more for improved waste collection service as found by Padi et al [15].…”
Section: Factors Influencing Amount Of Money That Households Are Willsupporting
confidence: 82%
“…7.7 (0.08 US$) per month. This positive relationship is also supported by other similar studies [15,19,30,31,33].…”
Section: Factors Influencing Amount Of Money That Households Are Willsupporting
confidence: 81%
See 1 more Smart Citation
“…To makes a meaningful development within the demarcation of local council, the needs and wants of the inhabitants' fulfilment represents the activeness of the local councils. In Malaysia the position of local councils allow them to take the responsibility of providing services to the local community [55,82,85,94]. If the municipal services delivered by the local councils are perceived as poor, the future of good governance and professional images of this local councils will be at stake [85].…”
Section: Citizen Satisfactionmentioning
confidence: 99%
“…In fact, in the context of development, people who use the input of energy, materials and technology to carry out daily activities in a city could create urban ecosystem deterioration intentionally or unintentionally (Jahi, 1996;Hussain & Ismail, 2013). Even everyday activities by human development in a town have created too much problems to the ecosystem despite the positive impact of the development (Hassan, Awang, & Jaafar, 2006;Pini, River, & McKenzie, 2007;Subhan, Ghani, & Joarder, 2014). The beneficial effects left by urban development such as an opportunity increase to quality of life, economic growth and physical development of urban city are certainly needed by society.…”
Section: Introductionmentioning
confidence: 99%